Adam und Embryo Ein Beitrag zur Erforschung der Adamsgeschichte in jüdischen, christlichen und islamischen Texten bis zum Ende des ersten Jahrtausends - Eich, Thomas; Doroftei, Doru Constantin (Recht, Ethik und Gesellschaft im Vorderen Orient | Law, Ethics and Society in the Middle East, 2023)
This book critically analyzes the notion that there are passages in the 7th-century text of the Qur'an that reflect medical ideas of the time about the origin of human beings through pregnancy. It turns out that the Qur'an draws on a rich heritage of motifs, on the one hand baptismal theological motifs that had developed by the 7th century and on the other hand Jewish-Christian polemical debates about the nature of Jesus. The unquestionable embryological passages of the Qur'an text are to be located in this polemic, in which an image known from Jewish-Palestinian texts of the 6th century is central: the growth of every embryo occurs in the same way as God created the first human being. The image of "Adam and Embryo" accompanied the early Islamic intellectual history for several centuries before it gradually fell into oblivion.